Parents' Weekend. Photo 134 - Sobecki, Nicki (Tufts Archival Research Center, 2008)
Parents' Weekend. Civil War Encampment/Re-enactment. See how soldiers lived during the Civil War and watch as they practice for battle. Drill demonstrations and presentations on camp life are scheduled throughout the day. Tisch Library Lawn, 9 a.m.-4 p.m.